Solar Physics and Space Weather Instrumentation V 2013
DOI: 10.1117/12.2027508
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the corona with the solar probe plus mission: the wide-field imager for solar probe+ (WISPR)

Abstract: The Solar Probe Plus (SPP) mission scheduled for launch in 2018, will orbit between the Sun and Venus with diminishing perihelia reaching as close as 7 million km (9.86 solar radii) from Sun center. In addition to a suite of in-situ probes for the magnetic field, plasma, and energetic particles, SPP will be equipped with an imager. The Wide-field Imager for the Solar PRobe+ (WISPR), with a 95º radial by 58º transverse field of view, will image the fine-scale coronal structure of the corona, derive the 3D struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…Opposite to the early general belief that CMEs were spherical bubbles holding rotational symmetry (e.g., Crifo et al 1983) supported by observations of Earth-directed circular halo CMEs (e.g., Howard et al 1982), a number of studies have indicated that many CMEs (if not all, see Vourlidas et al 2013) are organized along a major axis. Moreover, they present a topology consistent with that of a twisted magnetic flux rope in agreement with in situ detections of MCs.…”
Section: Introductionmentioning
confidence: 94%
“…Opposite to the early general belief that CMEs were spherical bubbles holding rotational symmetry (e.g., Crifo et al 1983) supported by observations of Earth-directed circular halo CMEs (e.g., Howard et al 1982), a number of studies have indicated that many CMEs (if not all, see Vourlidas et al 2013) are organized along a major axis. Moreover, they present a topology consistent with that of a twisted magnetic flux rope in agreement with in situ detections of MCs.…”
Section: Introductionmentioning
confidence: 94%
“…Solar Wind Electrons Alphas and Protons (SWEAP) Suite will measure the thermal plasma that constitutes the bulk of the solar wind. The Wide-field Imager for Solar Probe Plus [3] (WISPR), is a white light imager that will image the heliosphere that the spacecraft will fly through. In addition, there is an SPP observatory scientist that serves as a liaison between the broader scientific community and the mission's Science Working Group (SWG).…”
Section: Solar Probe Plus Scientific Investigationsmentioning
confidence: 99%
“…Heliospheric imagers very similar to the STEREO/HIs are currently being developed for the next generation of solar spacecraft observatories (SoloHI for Solar Orbiter [84] and WISPR for Solar Probe Plus [85]) that are scheduled for launch near the end of the decade. In addition, other more general concepts and guidelines have been proposed for possible future missions [86].…”
Section: Considerations and Concepts For Future Heliospheric Imagersmentioning
confidence: 99%